Fabrication and Characterization of Passive Sampler using Polymeric Inclusion Membrane (PIM) as Diffusion Layer for Phosphate Measurement - Barlah Rumhayati; Adam Wiryawan; Layta Dinira; Sakhiyah Afifah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
The PIM-passive sampler is a passive sampler using PIM as a diffusion layer. This research aimed to optimize the concentration of PIM plasticizer and the concentration of phosphate ions in bulk solution to produce a PIM-passive sampler for phosphate measurement with high accuracy. In this study, a passive sampler was made of a 15 ml glass bottle containing 0.2 M H2SO4 solution as the receiving phase and PIM as a diffusion membrane. PIM was prepared by mixing polyvinyl chloride (PVC) as the base membrane, Aliquat 336-Cl as a carrier, and 1-decanol as a plasticizer. Sampling was done by immersing the passive sampler in the bulk phase solution for three hours. The phosphate concentrations in bulk and receiving phases were determined regularly every 30 minutes using the visible spectrophotometric method at a wavelength of 690 nm. The results showed that the optimum concentration of 1-decanol for PIM was 15% w/w. The higher the plasticiser concentration, the PIM was oily, thus preventing the analyte from contacting the extractant. The range of phosphate ion concentrations in the sample that the PIM-passive sampler could detect was 0.1-1.3 mg P/L. The calibration curve for phosphate measurement was CTWA = 1.0664. Cs – 0.0088 with a correlation coefficient (R2) was 0.9998. This shows that the PIM-passive sampler can be used for the measurement of phosphate ions with high accuracy.